PEMANFAATAN BIJI Nigella sativa DALAM TERAPI PENYEMBUHAN KANKER DAN GANGGUAN METABOLISME - Jamil, Ahmad Shobrun (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2010)
The seed of Nigella sativa has long time ago employed as medicinal remedy for numerous disorders. N.sativa has active compounds in its seed likes nigellisine, nigellidine, nigellimine-N-oxide, thymoquinone, dithymoquinone, thymohydroquinon, nigellone, thymol, arvacrol, oxy-coumarin, 6-methoxycoumarin, 7-hydroxy-coumarin, alpha-hedrin, steryl-glucoside, flavonoids, tannins, essential amino acid, ascorbic acid, and minerals. The seed has various curative activities. As body immunity stimulator by stimulating the formations of bone marrow and many kind of antibody cells, antihistamine, anti-hypertension, anti-inflammation, antimicrobial activities by protecting bodies from viruses and decreasing the risk of infections, anti-diabetic (metabolic syndrome), and anti cancer. These papers have to discuss deeper about the beneficial aspect of N. sativa seed against metabolic syndrome and cancer. Based on several research known that N. sativa has potential to decrease total cholesterol, low density lipoprotein and blood glucose level. This seed also has potential to maintain the homeostatic of blood vessels as the backbone of the circulatory system in the body. At the cancer case, this seed substances has potential to decreasing the development of cancerous cells, kills the cells by enhances its apoptotic programs and also lessening the metastasis of the cancer cells.Â Keywords: cancer, metabolic syndrome, Nigella sativa